ACTUAL PROBLEMS OF REALIZATION OF THE RIGHT OF PERSONAL PROTECTION OF THE ACCUSED IN THE CONTEXT OF THE REQUIREMENT FOR A TERM FOR PRE-TRIAL INVESTIGATION ACCORDING TO THE BULGARIAN CRIMINAL PROCEDURE CODE. - Lyuboslav LYUBENOV (Challenges of the Knowledge Society)
The present scientific publication represents an attempt for clarification the question, how affects the principle of objective truth and the right of personal protection of the accused person to carry out the pre-trial investigation in an explicity regulated by law period of time? For this purpose, is made an obserbance of Art.234, par.7 of the Criminal Procedure Code of the Republic of Bulgaria and the legal consequences. Based on the understanding that the defendant’s right to personal protection is in its broadest sense, a recognized and guaranteed opportunity for personal, active participation in criminal proceedings we have mainly dealt with the issue of excluding important evidence of justification only because they were collected beyond the period of investigation and over the forms of limiting the personal activity of the accused person in the preliminary stage of trial through the investigation period itself. In the context of the problems described, a case- law of the European Court of Human rights has also been discussed. In the final part of the report are made theoretical conclusions on the basis of which were formulated proposals for improvement of the Bulgarian Code of Criminal Procedure.